Equity issues in varietal dissemination through farmers' fairs (Kisan Melas) in Punjab, India - Singh, J; Malhi, S.S.; Witcombe, John R.; Virk, Daljit S. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
In the Punjab state of India, grain production has rapidly increased. One factor in this increase has been the fast adoption of new varieties. Punjab Agricultural University (PAU) has played a major role in distributing certified seed of new vanities to the farmers of the stale, Most of Ihe seed is distributed by sales al farmers' fairs (kisan melas) held al PAU and its regional research stations. In this study, equity issues in the sale of wheal seed were examined in farmers' fairs held in September 1999.